The Effect of Government Accounting Standards Understanding, Human Resource Competence, and Accounting Information Systems on Financial Reporting Quality in the Bandung City Government - Karima Islahia Fatimah; Budi Hendaris (SAFE-Network, 2026)
This research applies a quantitative causal–associative design to investigate how Public Sector Accounting Framework knowledge, Public Sector Personnel Capability, and the utilization of accounting information systems relate to the quality of financial reports in the Bandung City Government. Data were gathered primarily through questionnaire distribution, supported by interviews to enrich the analysis. The study involved 124 respondents representing financial management units within the Bandung City Government. Data processing and hypothesis testing were performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The empirical results show that, individually, Public Sector Accounting Framework knowledge and Public Sector Personnel Capability have a significant influence on financial reporting quality, whereas the accounting information system variable does not exhibit a significant standalone effect. In contrast, the simultaneous analysis confirms that all explanatory variables jointly affect the quality of financial reports. Moreover, the findings provide practical implications for assessing the institutional readiness of the Bandung City Government in anticipating future developments in financial reporting regulations.